Correlation of vitamin D serum level and quality of life in asthma patients - Dzenan Halilovic; Jasmina Nurkić; Senahid Trnačević; Midhat Nurkić; Eldina Halilović; Ekrema Mujarić (Medicinski glasnik, 2025)
Aim: Moderate to severe asthma patients with sufficient and insufficient vitamin D serum level, respectively, were assessed with quality of life questionnaires before and after treatment with vitamin D added to their standard asthma treatment. Methods: Patients with moderate to severe asthma have been divided into two groups based on a serum level of vitamin D as sufficient or insufficient level of vitamin D, respectively. During 12 months, a total of 120 patients with sufficient level of vitamin D as well as 120 patients with insufficient level were given treatment with 2000 IU vitamin D for a three-month period. Quality of life of all patients was assessed by Asthma Control Test (ACT), Asthma Quality of Life (AQOL) and the physician's assessment expressed through the Global Evaluation of Treatment Effectiveness (GETE), which were performed before and after the treatment with Vitamin D. Results: Values of ACT and AQOL were higher after the treatment with vitamin D in both groups of patients. Values of GETE were lower after the treatment with vitamin D in both groups. All assessed components, psychological, physical, as well as the subjective feeling of control of the disease assessed by treating physicians, showed improvement after treatment. Conclusion: Adding vitamin D in the treatment regimen of moderate to severe asthma patients improves quality of life and general asthma treatment effectiveness.
Keywords: ACT; AQOL; GETE; obstruc-tive dis-ease; vitamin D deficien-cy